Circulating endothelin in acute ischaemic syndromes. Issue 5 (May 1992) - Ray, S G; McMurray, J J; Morton, J J; Dargie, H J
Abstract : BACKGROUND--Endothelin is an extremely potent vasoconstrictor that may have a role in the pathogenesis of acute myocardial ischaemia. Atrial natriuretic factor is an endogenous antagonist of endothelin. To find the pattern and possible importance of circulating endothelin in ischaemic heart disease, concentrations in normal controls and those in patients with stable and unstable angina, acute myocardial infarction, and chronic cardiac failure were compared. The relation between circulating concentrations of endothelin and atrial natriuretic factor in the aftermath of myocardial infarction was also examined. METHODS--Eighteen patients with acute myocardial infarction, 10 with unstable angina, 10 with stable angina, 12 with chronic cardiac failure, and 10 normal controls were studied. Endothelin concentration was measured in venous plasma by radioimmunoassay. In patients with acute myocardial infarction simultaneous concentrations of endothelin and atrial natriuretic factor were measured on admission and at one, four, and 24 hours. RESULTS--Mean concentrations (SEM) of endothelin were 5.72 (0.19) fmol/ml in controls, 6.56 (0.48) fmol/ml in stable angina, 6.41 (0.48) fmol/ml in unstable angina, and 13.83 (0.95) fmol/ml in chronic cardiac failure. In acute myocardial infarction concentrations were 8.81 (0.69) fmol/ml on admission, 11.85 (1.02) fmol/ml at one hour, 11.88 (1.10) fmol/ml at four hours, and 7.30 (0.49) fmol/ml at 24 hours. Concentrations of atrial natriuretic factor at the same times were 68.1 (13.1) pg/ml, 8.4 (1.5) pg/ml, 24.4 (4.1) pg/ml, and 42.0 (6.9) pg/ml. CONCLUSIONS--Plasma endothelin is raised in chronic heart failure and in the aftermath of acute myocardial infarction but not in stable or unstable angina. After myocardial infarction endothelin concentrations are raised whereas concentrations of atrial natriuretic factor are relatively low. The role of endothelin in the pathogenesis of acute myocardial infarction and its interactions with other humoral factors require further investigation.